Generalization strategies used by 6 and 7-year-old students when solving a geometric pattern task (Edma 0-6: Educación Matemática en la Infancia, 2021)
Recent research in Mathematics Education has shown that children from an early age can express algebraic thinking and highlight the importance of providing contexts that help them develop it. In order to deepen in these aspects, this project explore near, far and inverse generalization strategies shown by six children aged 6 and 7 when solving a task that involves a geometric pattern. The results show a preference for counting and recursive strategies for obtaining near terms, with some evidence of more advanced strategies for far generalization. In addition, it is shown how two of the students were able to find the inverse functional relationship for a specific value using a variety of strategies. The results coincide with similar studies that show that students of this age can solve tasks that involve functional relationships and provide information about their reasoning when trying to find the different terms of the sequence. Finally, in order to help the students develop this type of reasoning the importance of working with geometric pattern tasks together with concrete material familiar to them is highlighted.
Keywords: Algebraic thinking; Early algebra; Geometric patterns; Generalization